Design and analysis of a dual-band THz metamaterial sensor with high refractive index sensitivity - Lu, Xuejing; Ge, Hongyi; Jiang, Yuying; Zhang, Yuan (Frontiers in Physics, 2022)
A terahertz metamaterial comprised of an array of cross rectangular split-ring resonators (CRSRR) was proposed and analyzed for sensing applications, and it exhibited two resonances in the frequency range of 0.2-3 THz. The resonant frequencies of different resonant modes were explained using equivalent circuit models. Furthermore, the influence on equivalent capacitance and inductance of the circuit with respect to different geometrical dimensions of the CRSRR structure were analyzed, and the results indicated that the resonant frequencies of the proposed metamaterial can be designed as the desired value by adjusting the CRSRR unit geometry. In addition, the sensing performances of the metamaterial were calculated based on the optimized structure, showing that it had high refractive index sensitivity of 309 and 730 GHz/RIU at two resonant frequencies, respectively. Meanwhile, such ability to operate at two frequency bands enabled the designed sensor could characterize the identical samples at different frequencies, thereby increasing the sensing sensitivity and decreasing the impact of environmental disturbance. Our study opens up new prospects in the design of terahertz metamaterial sensors with high sensitivity in a multi-band range, which is essential to meet increasing needs in terahertz sensing.